A wideband lumped circuit model of eddy current losses in a coil with a coaxial insulation system and a stranded conductor. - Holmberg, P.
This paper presents a wideband lumped circuit model of eddy current losses in a coaxially insulated coil. The wide frequency range of the model is achieved by means of dual and extended Cauer circuits, which are equivalent circuits used for eddy current modeling. The complete lumped circuit reproduces the expected response well. However, because of resonances in the coil, the model cannot be experimentally verified for higher frequencies than 5 kHz. The parameters of the lumped circuit are mainly acquired from field calculations and aggregate the eddy current losses in the stranded conductor of each turn. The aggregate considers the contact resistance between the strands. The eddy current model can be used as a part of a complete model of the coil intended for, e.g., lightning impulse simulations, as the winding is discretised into short pieces. The results of the paper are of special interest for coaxially insulated electric machines, such as the commercially available Powerformer? and Dryformer?.
Keywords: Dryformer; Powerformer; Circuit transient analysis; Coaxial insulation system; Coaxially insulated electric machines; Coil; Complete lumped circuit; Contact resistance; Dual Cauer circuits; Eddy current losses; Eddy current modeling; Electromagnetic transient analysis; Equivalent circuits; Extended Cauer circuits; Lightning impulse simulations; Polymer insulation; Resonances; Skin effect; Stranded conductor; Wideband lumped circuit model